2018
DOI: 10.3389/fimmu.2018.02306
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoints as Therapeutic Targets in Autoimmunity

Abstract: Antibodies that block the immune checkpoint receptors PD1 and CTLA4 have revolutionized the treatment of melanoma and several other cancers, but in the process, a new class of drug side effect has emerged—immune related adverse events. The observation that therapeutic blockade of these inhibitory receptors is sufficient to break self-tolerance, highlights their crucial role in the physiological modulation of immune responses. Here, we discuss the rationale for targeting immune checkpoint receptors with agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 90 publications
(89 reference statements)
0
76
0
Order By: Relevance
“…Agonist antibodies and Fc-fusion proteins that engage co-inhibitory receptors have been successful in treating murine models of autoimmunity. 119 For example, cells from the draining lymph nodes of mice treated with agonistic anti-TIGIT antibodies showed reduced cell proliferation and proinflammatory cytokine production after restimulation with MOG-peptide. Moreover, the severity of EAE was reduced in treated mice accompanied by decreased frequencies of IL-17-producing lymphocytes in the CNS.…”
Section: Therapeutic Induction Of Exhaustion In Autoimmune Diseasesmentioning
confidence: 99%
“…Agonist antibodies and Fc-fusion proteins that engage co-inhibitory receptors have been successful in treating murine models of autoimmunity. 119 For example, cells from the draining lymph nodes of mice treated with agonistic anti-TIGIT antibodies showed reduced cell proliferation and proinflammatory cytokine production after restimulation with MOG-peptide. Moreover, the severity of EAE was reduced in treated mice accompanied by decreased frequencies of IL-17-producing lymphocytes in the CNS.…”
Section: Therapeutic Induction Of Exhaustion In Autoimmune Diseasesmentioning
confidence: 99%
“…Checkpoint molecules regulate T cell activation (Box 5) and conceivably such molecules can be therapeutically modulated in autoimmune diseases [35,36]. The narrow phenotype of gluten-specific CD4 + T cells in CeD includes expression of the inhibitory molecules Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and Programmed death 1 (PD-1) and the stimulatory molecules OX40, CD28 and Inducible T cell COStimulator (ICOS) (Box 3).…”
Section: Targeting Immune Checkpointsmentioning
confidence: 99%
“…Here the mechanism could be to dampen the disease-driving T cell response. Agonists of inhibitory checkpoint molecules have shown efficacy in different autoimmune mouse models [36]. The CTLA-4-Fc-fusion protein Abatacept, which probably acts by outcompeting the CD28:CD80/CD86 binding, serves as an indirect antagonist of this stimulatory checkpoint molecules.…”
Section: Targeting Immune Checkpointsmentioning
confidence: 99%
“…It was postulated that these polymorphisms affect receptor signaling and may be associated with ABDs susceptibility. Recent investigative efforts included the identification of mutations in genes encoding immunological molecules and their possible associations with pathological autoimmune response in various dermatoses [10,25]. Previous reports indicated that CD32B polymorphisms may be associated with systemic lupus erythematosus [26].…”
Section: Discussionmentioning
confidence: 99%